Features of Green Supply Chain Management for Investment Projects in the Recreational Territories of the North Caucasus Republics - Dzobelova Valentina Batrazovna; Irina Anatolievna Dikareva; Lida Kureyshovna Tochieva; Bella Movsurovna Musayeva; Valery Safarbievich Misakov (International Journal of Supply Chain Management, 2020)
Abstract- The term sustainable or green supply chain refers to the idea of integrating sustainable environmental processes into the traditional supply chain. The development of most industries in the real sector of the national economy is accompanied by a buildup of negative environmental impact. This situation, of course, requires an objective environmental and economic assessment and prediction of possible impact scenarios. In the North Caucasus, a number of recreational regions (Kabardino-Balkaria, Karachay-Cherkessia, North Ossetia-Alania, Chechen Republic) contain promising deposits of tungsten, molybdenum, zinc, oil, etc. Moreover, those deposits are located in places where ecosystems are very vulnerable, which causes the need for a special approach to ensure environmental requirements in the implementation of investment projects in the environmental management system. In today's realities, it is obvious that the development of the above strategically important deposits will not be performed without the participation of foreign partners, which is associated with certain features of the strategic management of an investment project, the development and approval of project documentation, etc. Undoubtedly, here it is necessary to foresee the possibility of the formation of a number of fundamental differences in Russian and foreign requirements for conducting socio-ecological and economic examination of investment projects. All this requires a certain harmonization between Russian and international requirements, unification of methods for organizing environmental support for investment projects implemented within the boundaries of specially protected natural territories of the North Caucasus.